THE ROLE OF DIGITAL TOOLS IN ELT MATERIALS DEVELOPMENT - Rabbimqulova Ruhshona Zokir qizi; Hotamboyeva Zarnigor Bobirjon qizi; Akramova Dinara Bahrom qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In recent years, digital tools have significantly transformed the field of English Language Teaching (ELT), especially in the development of teaching materials. This paper explores the role of digital technologies such as online platforms, interactive applications, multimedia resources, and artificial intelligence in enhancing ELT material development. The study highlights how these tools support teachers in creating more engaging, personalized, and effective learning content. Digital tools also increase learner motivation and provide opportunities for autonomous learning. However, the paper also discusses challenges such as technical limitations and the need for teacher training. Overall, digital tools play a crucial role in modern ELT by improving the quality and accessibility of educational materials.